1999
DOI: 10.1577/1548-8675(1999)019<0249:eossar>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Size and Rearing Method on Muskellunge Survival in Chautauqua Lake, New York

Abstract: We examined the effects of rearing method and size at stocking on the survival of muskellunge Esox masquinongy in Chautauqua Lake, New York. Since 1961, changes in rearing methods have coincided with declining abundance of adult muskellunge. In particular, a change from pond rearing to trough rearing coincided with declining catches of adult muskellunge in pound nets. The decline was only partly reversed by changes from trough rearing to pond finishing of fingerlings. Changes in survival to age 5 from 1961 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Density dependent mortality occurs in many self-sustaining fish populations of many species (Myers and Cadigan 1993;Myers et al 1997), and also occurs with stocking density in individual waters (McKeown et al 1999;Sutlea et al 2004). Our findings agree with those of McKeown et al (1999), who suggested that carrying capacity may limit the success of stocked fish if the stocking density is above some level in any individual water. Our results suggest that density-dependent mortality associated with walleye stocking rate may be generalized across waters.…”
Section: Discussionmentioning
confidence: 99%
“…Density dependent mortality occurs in many self-sustaining fish populations of many species (Myers and Cadigan 1993;Myers et al 1997), and also occurs with stocking density in individual waters (McKeown et al 1999;Sutlea et al 2004). Our findings agree with those of McKeown et al (1999), who suggested that carrying capacity may limit the success of stocked fish if the stocking density is above some level in any individual water. Our results suggest that density-dependent mortality associated with walleye stocking rate may be generalized across waters.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing hatchery fish to larger sizes leads to increased survival upon release (Gunn et al. 1987; McKeown et al. 1999; Yule et al.…”
Section: Introductionmentioning
confidence: 99%
“…Stocking studies that attempted to identify optimal ages for release into natural environments reported mixed results with respect to survival based on age at stocking (Elrod et al 1988;Margenau 1992;Secor & Houde 1998;Amtstaetter & Willox 2004). Rearing hatchery fish to larger sizes leads to increased survival upon release (Gunn et al 1987;McKeown et al 1999;Yule et al 2000), and probabilities of juvenile survival may be non-independent among members of the same family. Accordingly, if different gamete collection methods result in different levels of mean coancestry relative to the number of adults contributing to individuals that survive to the time of release, then evaluations of different gamete/larval collection methods are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to account for variation among species for behaviors that can be modified, it may be necessary to have an understanding of ecology and life history traits for a particular species. While overhead cover and structure in rearing tanks may stimulate appropriate feeding or territorial behavior for salmonid fry (Berejikian et al 2000), other species, such as esocids, may benefit from pond rearing with live prey prior to stocking to reduce predation vulnerability and improve feeding success (Szendrey and Wahl 1995;Wahl 1995;McKeown et al 1999).…”
mentioning
confidence: 99%